(untitled) (Journal of the College of Basic Education, 2023)
The contemporary Islamic awakening is considered one of the important phenomena in the Islamic world. It started since the beginning of the twentieth century and developed in the subsequent years until it has become today one of the most important issues, especially after it crystallized into a complete project for life management adopted by a wide public base that has achieved its implementation in regions and seeks to achieve it in regions, and seeks to achieve it in other regions, and after the first international conference of the Islamic Awakening was held in Tehran from 17-18 / September 2011 in the presence of a large number of thinkers, intellectuals and politicians of the Islamic nation, as there was a great opportunity to raise the concerns and problems of the nation and shed light on the Islamic awakening from Its various aspects, especially what has been termed the Arab Spring revolutions. This motivated us to write this research, in which we will address the concept of Islamic awakeningFreedom and human rights in the opinion of the distinguished elite of the leaders of the Islamic Awakening.Problems facing the development of the Islamic world.Possible results of the growth of the phenomenon of Islamic awakening.We will try, through researching the aforementioned paragraphs, to clarify the most important challenges that we see as having a clear impact on the course of the Islamic awakening and its escalation, and its occupation of the position it deserves in the life of the nation after facts and events have proven the futility and failure of Marxist, nationalist and liberal currents, and their inability to lead life in the directions that achieve human happiness.